PENGAYAAN MATERI PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS DI ACEH JAYA - M Yusuf; Ismail Darimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The enrichment of teaching materials is a very important thing that must be done by subject teachers in order to improve the quality of good and quality education. The research subjects in this study were high school Islamic religious education teachers in the 2019-2020 school year. Descriptive analytical research uses observation and interview data collection techniques. Analysis through three stages, namely Data Reduction, data presentation, and drawing conclusions. The results showed that the development of teaching materials that teachers develop materials using media in accordance with the material to be taught. Teachers in enriching teaching materials include giving examples, directly practicing teaching materials, using media, using media that has been available in schools in the form of printed materials in the form of books, pictures, maps while other materials or materials conveyed are recorded on the blackboard. Barriers faced by the teacher in enriching teaching materials other than the teacher's own knowledge about the development of teaching materials, laboratory-based learning infrastructure facilities are also not available.